A Literature Highlight on Teachers Competency Level in Teaching Special Class on Quranic Recitation and Memorization Skills (KKQ) - Zulkifli Abd Mubi; Haziyah Hussin; Sabri Mohamad (Jurnal Pendidikan Agama Islam, 2024)
Purpose – Competent teachers have the ability to confront and design high-quality instruction that plays a pivotal role in nurturing the multifaceted development and equilibrium of students. Nevertheless, some research has revealed that there is a need for enhancement in teachers' competencies with regards to their knowledge, skills, and attitudes. In this context, a comprehensive review of the literature was undertaken to examine the many themes associated with the competence of teachers in instructing the Special Class on Quranic Recitation and Memorization Skills (KKQ) inside educational institutions. Methods – The present study employs a qualitative approach, utilizing the design of document content analysis to examine journal articles. Four widely utilized databases, notably Google Scholar, ResearchGate, Mendeley, and Malaysian Citation Index, are employed to conduct searches for scholarly publications released within the period of 2019 to 2023. In this study, a comprehensive analysis was conducted on a set of 30 publications that satisfied the established criteria. Findings – The analysis revealed the identification of six distinct themes pertaining to teacher competencies. These topics encompassed pedagogical knowledge, content knowledge, curriculum knowledge, knowledge of the background of students, and teacher skills. Research implications – The findings of this study suggest that stakeholders, at both the Ministry of Education Malaysia level and the implementation level of the program in schools, should prioritize the Special Class on Quranic Recitation and Memorization Skills. This attention is necessary to enhance and improve the competency of teachers, ultimately leading to the successful achievement of the goal of producing Quranic-skilled and passionate students. Originality/value – Further research is required to assess the proficiency of teachers in employing e-learning and multimedia tools for KKQ teaching.